In-House SEO: Taming the Challenges to Win in Search - Mitchell, Melanie (Pearson, 2012)
Take charge of SEO in your organization: do what it takes to get outstanding search results that translate into improved business performance! World-renowned search strategist Melanie Mitchell covers everything you need to know to build a rock-solid foundation for search success in your organization. Named several times as a "top in-house SEO" by Natural Search Blog, Mitchell draws on her immense experience to help you tame the organizational and political challenges you'll face in building a world-class SEO program. Mitchell shows how to align your organization departmentally, politically and culturally around winning in search... demonstrate what's at stake, convincingly explain the opportunity SEO offers, and get real executive buy-inches.. clarify where you stand and what you can realistically achieve. Next, she presents a six-step, start-to-finish plan for success, encompassing creating your core SEO team, establishing accountability, developing and providing training, setting internal SEO standards, providing the right tools, and measuring, tracking, and optimizing your effectiveness. From integrating business and technical tasks to crafting effective in-house SEO instruction to building real-time dashboards, Mitchell explains what to do, what not to do -- and where you can start today!